Finite element modeling of fiber reinforced polymer-based wood composites used in furniture construction considering semi-rigid connections : Primjena metode konačnih elemenata za modeliranje drvno-plastičnih kompozita ojačanih vlaknima za uporabu u konstrukciji namještaja s polukrutim vezovima - Zor, Mustafa (Array, 2020)
In this study, control samples of pine (Pinus slyvestris L.), beech (Fagus orientalis L.) and oak (Quercus petreae L.) species were obtained by using fi ber reinforced finger corner joints. Teknobont 200 epoxy and polyvinyl (PVAc) adhesives were used as glue. Bearing in mind the critical loads that may affect their use, experimental samples were tested under diagonal loads. Experimental samples were also analyzed by a computer program using the finite element method (FEM). Finally, experimental data were compared with the results of FEM. The comparisons clearly showed that experimental results and finite element solutions (SAP2000 V17) including semi-rigid connections are in good agreement. As a structural analysis program in furniture engineering designs, FEM can be preferred in terms of reliability and cost.